Novel developments in web-based learning technologies : tools for modern teaching - Karacapilidis, Nikos (Hershey PA : Information Science Reference, 2010)
'This book explores a series of issues related to the current state, objectives and future trends of collaborative learning'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Web-based instruction; Education -- Computer network resources; Teaching -- Computer network resources; Internet in education